2021
DOI: 10.3390/medicina57050445
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral Lower-to-Upper Limb Cross-Transfer Effect on Muscle Strength, Mechanical Power, and Lean Tissue Mass after Accentuated Eccentric Loading

Abstract: Background and Objectives: To investigate the effects of unilateral accentuated eccentric loading (AEL) on changes in lean mass and function of leg trained (TL) and ipsilateral non-trained arm (NTA) in young men and women. Materials and Methods: In a prospective trial, 69 Physically active university students (20.2 ± 2.2 years) were randomly placed into a training group (n = 46; 27 men, 19 women) or a control group without training (n = 23; 13 men, 10 women). Participants in the training group performed unilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 46 publications
2
23
0
Order By: Relevance
“…Our finding that, in the posttest, the response time of RM sequences of the LL was significantly faster in the LL group as compared to both the SO and NO groups is in line with our hypothesis that LL practice would improve UL performance compared to merely observing the same sequences of the light switches or observing nature films. This finding regarding the ipsilateral transfer of performance from LL to UL supports the findings of the few previous studies that investigated ipsilateral transfer of strength from the LL to the UL in healthy adults and youth [ 26 , 27 , 28 ], and the ipsilateral transfer of a motor skill (2D virtual “moving snake” task and star-line drawing task [ 29 ]) between proximal and distal effectors within the UL [ 18 , 29 ].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Our finding that, in the posttest, the response time of RM sequences of the LL was significantly faster in the LL group as compared to both the SO and NO groups is in line with our hypothesis that LL practice would improve UL performance compared to merely observing the same sequences of the light switches or observing nature films. This finding regarding the ipsilateral transfer of performance from LL to UL supports the findings of the few previous studies that investigated ipsilateral transfer of strength from the LL to the UL in healthy adults and youth [ 26 , 27 , 28 ], and the ipsilateral transfer of a motor skill (2D virtual “moving snake” task and star-line drawing task [ 29 ]) between proximal and distal effectors within the UL [ 18 , 29 ].…”
Section: Discussionsupporting
confidence: 87%
“…In contrast to the evidence concerning the intermanual transfer of the UL [ 13 22 ], very few studies have investigated ipsilateral transfer within the same UL (intramanual transfer) [ 18 , 25 ] and between limbs [ 26 28 ]. For example, transfer of a motor skill, in which the participants had to track the head of a snake (2D virtual “moving snake” task), has been found from the shoulder to the finger [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, despite a significant change in aerobic capacity after a 12-week concurrent training (moderate-intensity treadmill running training combined with resistance training (MICT + RT) or high-intensity treadmill interval training combined with resistance training (HIIT + RT)) intervention, handgrip strength did not change in the intervention (pre-post change; MICT + RT = −1.1 kg and HIIT + RT = 0.9 kg) and control (pre-post change: −1.3 kg) groups [ 40 ]. Previous studies reported increased muscle strength of the untrained upper extremities due to resistance training of the lower extremities (called the cross-education or cross-transfer effect) [ 41 , 42 ]. However, there are no studies of increased handgrip strength with the above lower-body training intervention.…”
Section: Resultsmentioning
confidence: 99%